2009
DOI: 10.1038/gene.2009.65
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphisms and distinct clinical phenotypes of hepatitis B carriers in Taiwan

Abstract: Vitamin D exhibits immunomodulatory and antiproliferative effects through vitamin D receptor (VDR) in chronic infections and cancers. We genotyped the BsmI (rs1544410), ApaI (rs7975232) and TaqI (rs731236) polymorphisms of VDR gene in 250 Taiwanese chronic hepatitis B virus (HBV) carriers who were categorized into six phenotypes. After adjustment for age and sex, the frequencies of the VDR B/b, B/a, B/T, B/a/T in patients with hepatitis flare(s) were lower than those without (7 vs 20%, P ¼ 0.009; 1 vs 9%, P ¼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 36 publications
2
39
1
Order By: Relevance
“…Polymorphisms of VDR may therefore influence the immunomodulation via 1,25(OH) 2 D. There are few studies that have examined the association of VDR polymorphisms with HBV infection. One study indicated that the Bsm I, Apa I, and Taq I polymorphisms of the VDR gene were associated with distinct clinical phenotypes in HBV carriers, but not with HCC development (Huang et al, 2010). An association between the VDR Taq I T allele and asymptomatic hepatitis B was also reported (Shan et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Polymorphisms of VDR may therefore influence the immunomodulation via 1,25(OH) 2 D. There are few studies that have examined the association of VDR polymorphisms with HBV infection. One study indicated that the Bsm I, Apa I, and Taq I polymorphisms of the VDR gene were associated with distinct clinical phenotypes in HBV carriers, but not with HCC development (Huang et al, 2010). An association between the VDR Taq I T allele and asymptomatic hepatitis B was also reported (Shan et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Single-nucleotide polymorphisms (SNPs) in the VDR gene on chromosome 12q12-q14 have been shown to be associated with distinct clinical phenotypes, except HCC (Huang et al, 2010), and severity of liver disease in HBV infection (Suneetha et al, 2006) with conflicting findings . The CYP27B1-1260 promoter polymorphism has been demonstrated to be associated with autoimmune diseases (Lopez et al, 2004;Bailey et al, 2007;Sundqvist et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain polymorphisms in the vitamin D receptor have been associated with occult hepatitis B infection, greater severity of hepatitis B associated liver disease, and a higher viral load [28][29][30][31]. The tumor necrosis factor-alpha (TNF)-α 308 allele and VDR ApaI A allele tend to occur more frequently in children with chronic hepatitis B virus infection, suggesting that the TNF-α and vitamin D pathways may be involved in the susceptibility to and outcome of hepatitis B virus infection acquired early in life [31].…”
Section: Hepatitismentioning
confidence: 99%